Latitudinal regionalization of epibenthic macroinvertebrate communities on rocky reefs in the Gulf of California. Issue 4 (20th April 2016) - Ulate, Karol; Sánchez, Carlos; Sánchez-Rodríguez, Alexandra; Alonso, David; Aburto-Oropeza, Octavio; Huato-Soberanis, Leonardo
ABSTRACT: We report on a latitudinal pattern in the structure and species composition of epibenthic macroinvertebrate communities on rocky reefs along a gradient of eight degrees of latitude in the Gulf of California. We provide quantitative evidence of a prominent shift in the taxa dominating these communities, particularly the sessile taxa (Cnidaria, Bivalvia, Annelida, Ascidiacea and Porifera). This pattern was not found in non-sessile taxa (Echinodermata, Decapoda, Cephalopoda, Gastropoda and Polycladida). Based on Bray–Curtis similarity and indicator species analysis we found that the macroinvertebrates of rocky reefs in the Gulf of California are distributed in three broad regions, indicating that sessile taxa are creating such a structure and are related to environmental changes tied to latitude. The northern region (>28° N) was a temperate zone with the coolest water in winter and highest chlorophyll a concentrations, where Octocorallia of the genus Muricea were the dominant taxa. The central region (∼24–28° N) had a mix of oceanographic features of the northern and southern regions and was dominated by Echinodermata in terms of species richness and density. The southern region (<24° N) is a subtropical zone with typically warm and clear water, and dominated by Hexacorallia (stony corals). The southern area was less diverse and had lower densities than the central and northern areas. These three communities correspond to known oceanographic discontinuities in the Gulf of California. This implies that future coastal management plans and conservation efforts in the Gulf of California must be regionalized to support their distinct ecological communities.